Knowledge, attitudes, and beliefs among dental students and faculty members regarding COVID-19 Vaccines in Dental Colleges of Haryana, India - A cross-sectional study - Neha Chauhan; B C Manjunath; Jadhav Sachin Kumar; Vipul Yadav; Bhavna Sabbarwal; Adarsh Kumar (Wolters Kluwer Medknow Publications, 2022)
Aim: To assess knowledge, attitudes, and beliefs among dental students and faculty members regarding COVID-19 vaccines in dental colleges in Haryana, India. Objectives: To assess knowledge level, attitudes, and beliefs differences among BDS, MDS students and faculty members and find association between knowledge and COVID-19 vaccine inoculation among study participants. Materials and Methods: A cross-sectional study was carried out among students and faculty members of dental colleges in Haryana, India. Data collection was done via an online questionnaire based on questions to assess the knowledge, attitude and beliefs regarding COVID-19 vaccines. Results: The present study comprised of 270 study participants, where majority, i.e., 81.5% have reported COVID-19 vaccine inoculation. The mean knowledge score of the participants was reported to be 5.54 ± 2.19. A significant difference was found in the mean knowledge score of faculty members (7.81 ± 1.69), MDS (6.72 ± 1.49), and BDS (4.39 ± 1.68) students. COVID-19 vaccine inoculation was found to be significantly associated with average knowledge score of participants (OR = 6.1, P < 0.01). Conclusion: Dental professionals have an adequate degree of knowledge and attitude level regarding COVID-19 vaccines and are generally optimistic about resolving the pandemic situation with the immunization.